An alternative splicing variant of PtRD26 delays leaf senescence by regulating multiple NAC transcription factors in Populus. Issue 5 (6th February 2021) - Wang, Hou-Ling; Zhang, Yi; Wang, Ting; Yang, Qi; Yang, Yanli; Li, Ze; Li, Bosheng; Wen, Xing; Li, Wenyang; Yin, Weilun; Xia, Xinli; Guo, Hongwei; et al.
Abstract: During leaf senescence, the final stage of leaf development, nutrients are recycled from leaves to other organs, and therefore proper control of senescence is thus critical for plant fitness. Although substantial progress has been achieved in understanding leaf senescence in annual plants, the molecular factors that control leaf senescence in perennial woody plants are largely unknown. Using RNA sequencing, we obtained a high-resolution temporal profile of gene expression during autumn leaf senescence in poplar ( Populus tomentosa ). Identification of hub transcription factors (TFs) by co-expression network analysis of genes revealed that senescence-associated NAC family TFs (Sen-NAC TFs) regulate autumn leaf senescence. Age-dependent alternative splicing (AS) caused an intron retention (IR) event in the pre-mRNA encoding PtRD26, a NAC-TF. This produced a truncated protein PtRD26 IR, which functions as a dominant-negative regulator of senescence by interacting with multiple hub Sen-NAC TFs, thereby repressing their DNA-binding activities. Functional analysis of senescence-associated splicing factors identified two U2 auxiliary factors that are involved in AS of PtRD26 IR . Correspondingly, silencing of these factors decreased PtRD26 IR transcript abundance and induced early senescence. We propose that an age-dependent increase of IR splice variants derived from Sen-NAC TFs is a regulatory program to fine tune the molecular mechanisms that regulate leaf senescence in trees. Abstract : An alternative splicing variant of NAC transcription factor PtRD26 is senescence-associated and regulates leaf senescence by repressing the DNA-binding activities of several NAC transcription factors.